Anomalous origin of the left anterior descending coronary artery from the right coronary artery with an interarterial and intramyocardial course: a long-term follow-up - Dursun, Aydin; Dogan, Nurullah; Ozkan, Hakan (The European Research Journal, 2016)
The left anterior descending coronary artery (LAD) originating from the proximal part of the right coronary artery (RCA) is a rare anomaly. An interarterial course for this anomaly is accepted as a ’malign course’ and surgical treatment is recommended. In a 66-year-old male patient, coronary angiography showed that the LAD originated from the proximal part of the RCA. Coronary computed tomographic angiography revealed that the LAD had an interarterial and intramyocardial course. The patient refused surgical treatment and has been followed-up without symptoms for the last 4 years with medical treatment. We wanted to contribute to the literature by reporting the long-term results of the medical treatment option for this anomaly with a malign course.